Peningkatan Efisiensi Jaringan Internet Menggunakan Firewall Fortigate Studi Kasus: PT. Jarvis Integrasi Solusi - Radityo, Daffa Bagus; Rustianto, April (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
PT Jarvis Integrasi Solutions often experiences unstable internet connections, which disrupt productivity. To address this, the company implemented SD-WAN (Software-Defined Wide Area Network) technology using the FortiGate 40F Firewall, replacing the previous Mikrotik gateway router. This SD-WAN feature enables smarter, more efficient network management by automatically adjusting settings based on connection quality and traffic load. The study used a quantitative method involving system design, SD-WAN configuration, and performance testing for failover and load balancing. Results showed that the FortiGate 40F significantly reduced downtime and improved network distribution. During failover tests, the system quickly switched to a backup path within 1–2 RTOs. Load balancing tests showed stable speeds, with inbound speeds of 7.21 Mbps and 7.17 Mbps and outbound speeds of 829.53 Kbps and 757.76 Kbps. Overall, SD-WAN optimized traffic usage and enhanced connection stability, offering clear benefits to the company's internet operations.